The Pullout Capacity of Polymeric Geogrids Embedded in Dune Sand-Tire Shred Mixture - El Berizi, Youcef (2025)
A Master of Science thesis in Civil Engineering by Youcef El Berizi entitled, “The Pullout Capacity of Polymeric Geogrids Embedded in Dune Sand-Tire Shred Mixture”, submitted in July 2025. Thesis advisor is Dr. Magdi El-Emam. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).